TEOLOGI KERUKUNAN BERAGAMA DALAM ISLAM (Studi Kasus Kerukunan Beragama di Indonesia) - Ghazali, Adeng Muchtar (Analisis: Jurnal Studi Keislaman, 2013)
Religious  affiliation  and cultural diversity has become potential sources of social conflicts in Indonesia.  As almost every existing religion has a truth  claim, all of it’s  believers   fell   obliged to proclaim   religious  teachings  and values in social and national life. Viewed in this  context  , the biggest  problem in Indonesia today is “ how  theology of existing religions define themselves among   other  religions . This article  is aimed at exploring   the concept of “Tasamuh / the principle of tolerance”   as one of  the theological  basis  of the  religious  consciousness    in Islam. The concept  of tolerance  in Islam  is so simple  and rational.  Islam requires its followers to establish  strict  limits in the context  of faith,  while maintaining  respect  for other’s  rights,  individually, socially and religiously.   Such an obligation  is made to keep its followers not to get stuck on syncretism.